Rancang Bangun Sistem Verifikasi Data Pengiriman Barang Berbasis Web Pada PT. Nitto Alam Indonesia - Taufiq, Rohmat; Melinda, Erika (Jurnal Teknologi Informasi (JUTECH), 2021)
Delivery Verification System is a system used to support a company's business growth. This system allowed the company to find out more about monitoring the intended shipment. PT. Nitto Alam Indonesia uses the ledger as a means of storing data and enters it into the computer during data processing and transmission. This fact created problems with the delivery schedule of goods that would need to be resolved. So, that the data input process was carried out twice by the admin staff. Therefore, the researcher designed a WEB-based delivery verification system that could assist the process of supervising the delivery of goods. In developing this system, the researcher used the PHP language, the system development method used Waterfall and UML as a tool. Building the delivery of this goods verification system could make it easier for drivers to see daily delivery schedules and allowed admins to provide reports on the status of shipments of goods successfully sent by the driver.